Observing documentary reading by verbal protocol - Fujita, Mariângela Spotti Lopes [UNESP]; Nardi, MIA; Fagundes, S. A. (Univ Sheffield Dept Information Studies, 2003)
Verifies the applicability to research on indexers' reading strategies of the process observing technique known as Verbal Protocol or Thinking Aloud. This interpretative-qualitative data collecting technique allows the observation of different kinds of process during the progress of different kinds of tasks. Presents a theoretical investigation into reading and into formal methodological procedures to observe reading processes. Describes details of the methodological procedures adopted in five case studies with analysis of samples of data. The project adopted three kinds of parameters for data analysis: theoretical, normative, empirical (derived from observations made in the first case study). The results are compared, and important conclusions regarding documentary reading are drawn.